74.4k views
0 votes
Graph ƒ(x) = -x + 2.

Click on the graph until the graph of ƒ(x) = -x + 2 appears.

Graph ƒ(x) = -x + 2. Click on the graph until the graph of ƒ(x) = -x + 2 appears.-example-1
Graph ƒ(x) = -x + 2. Click on the graph until the graph of ƒ(x) = -x + 2 appears.-example-1
Graph ƒ(x) = -x + 2. Click on the graph until the graph of ƒ(x) = -x + 2 appears.-example-2
Graph ƒ(x) = -x + 2. Click on the graph until the graph of ƒ(x) = -x + 2 appears.-example-3
Graph ƒ(x) = -x + 2. Click on the graph until the graph of ƒ(x) = -x + 2 appears.-example-4
User Telisha
by
5.6k points

1 Answer

1 vote

The slope-intercept form: y = mx + b

m - slope

b - y-intercept

We have f(x) = -x + 2 → y = -x + 2

m = -1 < 0 - function is decreasing

b = 2 → y-intercept = 2 → (0, 2)

Graph ƒ(x) = -x + 2. Click on the graph until the graph of ƒ(x) = -x + 2 appears.-example-1